Compelling reading skills in English classes through guided discovery strategy - Katherine Castro Vélez; Samantha Vega Zambrano; GABRIEL BAZURTO; Jhonny Villafuerte Holguin (PODIUM)
The purpose of this paper is to present a review of how the guided discovery strategy favors the development of reading comprehension skills and at the same time allows the acquisition of vocabulary and improvement of grammar in the teaching of English as a foreign language. The problem arises from a niche in which it found that the guided discovery strategy is conducive to develop reading comprehension skills, however a problem is generated by the motivation shown in students by the type of texts used for the development of reading comprehension, based on this it have raised the development of it research, considering that several studies indicate that compelling reading has a positive influence on reading skills. The methodology used consists of a bibliographic and documentary review of academic texts based on hermeneutic analysis. In this work it address issues related to the teaching of English as a foreign language, it focus on the development of reading skills through persuasive reading, it also highlight grammatical comprehension and comprehension of information input, and it point out some of the benefits of the application of the guided discovery strategy in the classroom, thus knowing that reading comprehension is of interest as a means of developing cognitive abilities and even helps them to become familiar with different reading styles, it also constitutes a significant learning process, which in successive stages will allow them to access information quickly and efficiently, achieving an independent mastery of their abilities, knowledge and skills when learning a language.